Polymorphism of PPARG (P12A), APOA1 (G75A), and APOE (C112A and A158C) Genes in Children with Obesity and Arterial Hypertension: A Case-Control Study - Olga P. Kovtun; Margarita A. Ustyuzhanina (Вопросы современной педиатрии, 2018)
Background. The genetic nature of a comorbid development of obesity and arterial hypertension (AH) in children is poorly studied. In this regard, it is important to study genes, the polymorphism of which is associated with disturbances in both metabolic processes and control of arterial pressure. Objective. Our aim was to study the association of polymorphisms P12A (rs1801282) of the PPARG gene, G75A (rs670) of the apolipoprotein A1 gene (APOA1), C112A (rs429358) and A158C (rs7412) of the apolipoprotein E gene (APOE) with the development of obesity and AH in children. Methods. The study included children with obesity and AH (case) and healthy children (control) aged from 10 to 17 years. Gene polymorphism was studied by polymerase chain reaction in real time. We determined blood concentrations of cholesterol and its fractions, triglycerides, apoA1, apoB, fasting glucose and glucose tolerance test for all children. Results. Groups of patients with obesity and AH (n = 69) and healthy children (n = 49) were comparable by age and sex. In the case group, there were more carriers of the A allele (25 versus 9% in the healthy group; p = 0.002) and the AA genotype (13% and 2%, respectively; df = 2, p = 0.031) of APOE C112A polymorphism. PPARG and APOA1 polymorphisms as well as APOE A158C polymorphism were not associated with the development of obesity and AH in children. The carriers of the APOE e2 allele had lower concentrations of low density lipoproteins and apoB in the blood; the carriers of the PPARG G allele had lower glycemia values, and the carriers of the A allele of APOA1 G75A polymorphism had higher glycemia values. Conclusion. The APOE C112A polymorphism is associated with a comorbid development of obesity and AH in children. The pathogenetic significance of PPARG and APOA1 polymorphisms warrants further investigation.